A Study on the Production Process Control of Zanthoxylum bungeanum Maxim Seed Kernel Oil without Trans-Fatty Acids - Zhongyi Yin; Shiyong Yao; Lixia Guo; Xuxu Zheng (Journal of Chemistry)
The process control of the production of Zanthoxylum bungeanum Maxim seed kernel oil (ZSKO) with no trans-fatty acids (TFAs) was investigated. Results revealed that drying temperature and time had a small effect on TFA formation in ZSKO. And high concentrations of sodium hydroxide solution had some effect on TFA formation in ZKSO, but there were no TFAs when the concentration of the sodium hydroxide solution was lower than 20% and even at boiling temperature for one hour. The roasting temperature and duration for Zanthoxylum bungeanum Maxim seed (ZS) should be properly controlled at 100°C for six hours or 150°C for two hours. ZS, which has a moisture content of 18%, was pressed four times (two hours) at less than 60°C, and ZSKO was obtained by collection through centrifuge separation. This contained 90.84% unsaturated fatty acids, which mainly include 32.49%  α-linolenic acid, 29.88% linoleic acid, and 27.52% oleic acids; and there was no TFA. Its acidic value and peroxide value conformed to China standards for edible oil. Therefore, ZKSO could be used as a healthy food for further development.